Transreal tracing: Queer-feminist speculations on disabled technologies. (April 2022) - Spiel, Katta
In a world where technologies often serve to amplify the persistent rendering of disability as an undesired deficit, what we need are empowering utopias concerning bodies, disabilities and assistive technologies. Specifically, I use Barad's article 'Transmaterialities: Trans*/Matter/Realities and Queer Political Imaginings' to illustrate how we might speculate on technologies that understand disabled bodies as affording potentials. The Transreal Tracing Device reimagines our bodies as surfaces of possibility, encouraging explorations into how disabled bodies do and could look like. The speculative device offers an opportunity for positive renegotiations of disabled bodies as malleable and desirable – as ontologically indeterminate and transcendent. In traversing theoretical approaches and using them to design queer-feminist utopias centring disabled people, the concept challenges dominant notions of disabilities and assistive technologies alike. I close by discussing implications for ability-based, participatory but even more so self-determined design, and how to shift the focus of disabled technologies towards potential, from support to appreciation, from isolation to kinship and, ultimately, from shame to pride.